Shared Creation of a Not-So-Human World: Review of Jocelyne Porcher and Jean Estebanez, eds., Animal Labor: A New Perspective on Human-Animal Relations - Sax, Boria (Humanimalia, 2020)
Jocelyne Porcher and Jean Estebanez, eds., Animal Labor: A New Perspective on Human-Animal Relations. Bleilefeld, Germany: Transcript Verlag, 2020. 200 pp. $87.49 (hb).